Klimatkrisen i klassrummet: Reflektioner kring användning av litteratur i undervisning om hållbar utveckling - Ulrika Andersson Hval; Celia Aijmer Rydsjö (Dalarna university, 2021)
This study shows how climate fiction can offer pedagogical opportunities for encouraging student agency as well as open up constructive discussions about the future in relation to social change and climate justice. In order to test a practical opportunity for such a productive conversation, and to draw out its didactic implications, Swedish teacher trainee students were asked to participate in a group discussion on how climate fiction may be used in the teaching of sustainability in upper secondary school. Specifically, they were requested to contribute to the framing and organization of the discussion of a work of climate fiction, The Marrow Thieves by Cherie Dimaline, but they were also asked to reflect on social dimensions of teaching about the climate crisis, such as climate psychology, democracy issues, equality and existential questions. Drawing on the students' discernments in the discussion, the study finds that insights from climate psychology concerning the importance of problem-focused and meaning-focused coping strategies to handle negative emotions such as worry, fear and hopelessness are relevant for literature didactics.